Effects of the program “Active and healthy older adults” on glycosylated hemoglobin levels and anthropometric status in patients with DM2 older than 59 years users of the ESSalud Ayaviri Medical Center, 2018 - Condori Choquepata, Patthy Milagros (2019)
Objective: to determine the effect of the program “active and healthy older adults” on the levels of hbA1c and anthropometric status in patients with DM2 older than 59 years users of the ESSalud Ayaviri Medical Center - 2018. Methodology: quasi-experimental design study, longitudinal since two study groups were formed with measures before and after the program, a sample of 113 older adults leaving 91 participants after the selection tests were applied, with 51 being the study group and 41 the control group. The program consisted of combined exercises (aerobic and anaerobic) alternating 15 “each for45 ‘in 5 days for a period of 12 weeks, plus a healthy eating talk for the control group. Results: before the application of the program, the physical activity level of the population was calculated, this being 60.4% of low activity followed by 39.6% of moderate activity. After the application of the program it was observed that there was no significant difference between 1st and 2nd measurement of HbA1c in elderly patients with DM2 (p> .05), likewise there was a clinical difference in the percentage values of 0.2% -1%, Regarding the BMI, there was a statistically significant difference between the first and second measurements (p <.05), as for the ICC a significant difference was obtained in the decreaseof its values during the second control as with the MNA test ( p <.05). Conclusion: at the level of significance there were no changes in the HbA1c values after the exercise program, but there were clinical percentage changes. On the other hand, if there was effect of the program on the patients’ atropometric changes, there was finally no effect through the ICC on HbA1c levels.